ZDY2-300LM Full Hydraulic Drilling Rig with Double Working Arms - SHAO Junjie, ZHANG Ning (Meikuang Anquan, 2020)
Aiming at the rapid and precise construction requirements for a large number of directional pre-borehole of roof cutting and pressure relief in coal mines, ZDY2-300LM full hydraulic drilling rig with double working arms is developed by means of variable amplitude mechanism with multiple degrees of freedom. LUDV hydraulic system is used to solve the problem of mutual interference when the two power heads work. AMESim software is used to build the simplified model and carry out the simulation research. The results show that the output flow and pressure are independent from each one and do not affect each other. The water way of two position three-way valve is adopted to solve the problem of backwater in the hole of loading and unloading drill pipe and increase the comfort of construction personnel. The test results show that the drilling rig has the advantages of fast angle adjusting speed, more freedom of luffing mechanism, accurate drilling positioning, good hole forming quality, and the construction efficiency meets the requirements of working face advance, which is 67.5% higher than that of other conventional non special drilling rigs.